2015
DOI: 10.5400/jts.2014.v19i3.151-159
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Indigenous N, P and K Supply for Rice Site Specific Nutrient Management in Buru Regency

Abstract: Rate of fertilizer that should be applied to rice soil based on Site Specific Nutrient Management (SSNM) depends on indigenous nutrient supply, its recovery efficiency, and the amount of nutrients requirement to achieve the yield target. Research on nutrient omission plot was conducted in farmers irrigated land on Waeapo plain, Buru Island. In this area, N, P, and K were the main limiting factors of rice growth and yield. To overcome the constraint, this assessment was conducted to determine the indigenous sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 12 publications
0
2
0
1
Order By: Relevance
“…Empty grain was determined by the number of tillers that grew before reaching the primordial phase. K deficiency can cause a high amount of empty grain and incomplete grain filling, and the plant growth is closely related to the balance of required nutrients (Susanto & Sirappa, 2015). Weight of 1000 grain seeds.…”
Section: Paniclesmentioning
confidence: 99%
“…Empty grain was determined by the number of tillers that grew before reaching the primordial phase. K deficiency can cause a high amount of empty grain and incomplete grain filling, and the plant growth is closely related to the balance of required nutrients (Susanto & Sirappa, 2015). Weight of 1000 grain seeds.…”
Section: Paniclesmentioning
confidence: 99%
“…It includes not only nutrients from the soil itself and nutrients mineralized by organic matter, but also residual nutrients from last season, from the environment, from biological and non-biological fixation, and deposition. The indigenous nutrient supply has become a primary consideration in fertilizer recommendations (Susanto and Sirappa, 2014). Previous studies found that N uptake was the most useful indicator of indigenous nutrient supply because it is easy to measure, is closely related to grain yield, and can provide information about productivity information and nutrient-use efficiency (Cassman et al, 1996b).…”
Section: Soil Indigenous Nutrient Supplymentioning
confidence: 99%
“…CNN merupakan salah satu model yang populer dan akurat untuk diimplementasikan dalam klasifikasi citra. Beberapa penelitian sebelumnya telah banyak mengimplementasikan CNN untuk melakukan klasifikasi citra, seperti klasifikasi citra makanan tradisional [15], klasifikasi citra tumbuhan [16,17], klasifikasi citra hewan [14,18], klasifikasi citra aksara Jawa [19,20], serta pengenalan objek dan karakter pada plat nomor kendaraan [21][22][23][24] dengan performa yang sangat baik.…”
Section: Geometrisunclassified